Establishing nurse practitioner clinical practicums: Addressing fiscal realities. Issue 11 (November 2019) - Delaney, Kathleen R.; Swartwout, Kathryn; Livesay, Sarah L.; Bavis, Margaret Perlia
Abstract : ABSTRACT: As demand expands for nurse practitioner clinical practicum sites, the supply of preceptors is decreasing. The traditional model of in-kind clinical training is losing its foothold for a variety of reasons. A looming question is how quickly a "pay to precept" norm will grow and what will be the costs. The pay for precepting movement is discussed including current trends, costs, and emerging compensation models. To adapt to this trend, alternative ways of drawing the precepting value proposition are suggested, particularly decreasing preceptor and site demands while increasing students' readiness to enter clinical practicum and tapping into faculty expertise to add value to the partnership. The authors provide suggestions on building a strategy for rethinking the structure of student precepting arrangements and compensation models.